Irradiação solar global com diferentes modelos para Alagoas - Santos, Cicero Manoel dos (2012)
The global solar irradiation (Hg) is variable major in several subject areas: Agriculture, Engineering, Climate and Renewable Energy. The total amount of incident Hg on the earth's surface can be accounted directly or indirectly. Directly is obtained from measurements made with operational instruments (pyranometers) and indirectly by estimating, by using empirical models. In this work, ten empirical models are used (nine based on air temperature and one in the sunshine duration) to estimate the global solar irradiation in eight sites from to Alagoas - Brazil, in scale hourly, daily and monthly. For models based on air temperature, two temperature regimes (air thermal amplitudes) (∆T1 and ∆T2) were evaluated to verify the influence on the models. Have been used air temperature, sunshine duration (n) and global solar irradiation (Hg) data, from September 2007 to December 2008 for fit of the models, and to validate the use data in 2009. The global solar irradiations (Hg) (MJm-2) were calculated from the integrations of the global solar irradiance (Rg) (Wm-2). In terms of global solar irradiation hourly average monthly (Hgh), the coefficients of the models shown to be dependent on the study site. The coefficients generated with daily data and monthly averages showed no difference to ΔT1 or ΔT2. For the model based on the sunshine duration (n), the adjusted coefficients are specifics to the estimated daily and monthly. In estimating hourly, the Hargreaves & Samani model (model 6) and the modified Hargreaves & Samani (models 7, 8 and 9) estimated the best monthly hourly global solar irradiation average (Hgh) in all sites analyzed. In the daily estimate, the Bristow & Campbell model (model 1) was more accurate than the model 6. However, the model 6 resulted with an average value of the population standard deviation of deviations (dpp) of 2,60, 2,79 and 2,79 MJm-2 for sites in the regions of the interior (Sertão), Hinterland (Agreste) and Coastal (Litoral) / Humid Area (Zona da Mata), respectively. Each month, the model 1 was more accurate than the model 6. The model based on the sunshine duration estimated the best daily global solar irradiation (Hgd) and monthly daily global solar irradiation average (Hgm), those based on air temperature, indicating low (dpp) and high coefficients of agreement (d).